التطوير التنظيمي للادارة المدرسية في سلطنة عمان: مدير مدرسة انموجا = Organizational development of the school management in the Sultanate of Oman: the principal of the school is a model - Rashid, Said; Al-Hidabi, Dawood Abdulmalek Yahya; Mohammed Ibrahim, Hossam El Din Elsaid (Emirates College of Educational Sciences in the United Arab Emirates, Dubai., 2019)
The present study aimed to identify the organizational development of the school Management in the Sultanate of Oman. The study used the historical method, and the analysis of documents was used in collecting data and information. The study reached the attention of the Ministry of Education in the Sultanate of Oman to the organizational development of school principals in five main areas: conditions of selection and candidacy, job duties, professional competencies, quality standards, and evaluation of job performance.